Preservation management for libraries, archives and museums (Facet, 2006)
This forward-looking collection charts the diversity of preservation management in the contemporary information landscape, and offers guidance on preservation methods for the sustainability of collections from a range of international experts. The authors are connected to a wide international network of professional associations and NGOs, and have been selected not only for their specific expertise, but for the contribution they are making to the future of preservation management. The chapters cover: managing the documentary heritage: issues for the present and future; preservation policy and planning; intangible heritage: museums and preservation; surrogacy and the artefact; moving with the times in search of permanence; a valuation model for paper conservation research; preservation of audiovisual media: traditional to interactive formats; challenges of managing the digitally born artefact; preserving cultural heritage in times of conflict; and access and the social contract in memory institutions redefining 'the collection' in the 21st century. There is urgent need for heritage management initiatives and robust disaster planning that will safeguard our cultural heritage and recognize the right of the end-user to ownership of it (Book cover)